√3x) + 6 = x
The 3x is under the radical sign.
√3x) + 6 = x
The 3x is under the radical sign.
Hello Lucinda,
I'm guessing 3x is under the radical sign. Here is the solution step by step.
√3x = x - 6
((3x)^{1/2})^{2} = (x - 6)^{2} (converted radical into exponential form)
(3x)^{2/2} = (x - 6)^{2}
3x = x^{2} - 12x + 36 ( (a - b)^{2} = a^{2} - 2ab + b^{2})
0 = x^{2} -12x -3x + 36
or x^{2} -12x -3x + 36 = 0
I hope this helps.
Thank you, this was very helpful.
Shawn may have misinterpretted the first term. It is sqrt(3X), not sqrt(3) x X. Therefore,
sqrt(3X) + 6 = X now subtract 6 from each side
sqrt(3X) = X - 6 now square both sides
3X = X^2 - 12X + 36 subtract 3X from both sides
0 = X^2 - 15X + 36 or
X^2 - 15X + 36 = 0 now factor or use quadratic formula. Factoring yields
(X - 3)(X- 12) = 0 now set each factor = 0
(X - 3) = 0 and X = 3 or (X - 12) = 0 and X = 12
You move terms w/ variables to one side and constant term to the other side:
sqrt(3) x -x = -6
Factor out x:
(sqrt(3)-1) x = 6
divide the (sqrt(3)-1) from both sides:
x = 6 / (sqrt(3)-1)
multiply sqrt(3)+1 to both numerator and denominator:
x = 3 (sqrt(3)+1).
Comments
Please confirm that you mean that only the 3 is under the square root sign, not the x. If that is the case, Shawn's method seems like the most straight forward.
Your problem is tagged "Completing the Square", which makes me wonder if there isn't a missing exponent.
Comment